Optimization of basic immunization coverage at Paku Alam - Hasanah, Siti Noor; Friscila, Ika; Wahdah, Rabia (Health Sciences International Journal, 2024)
Background: Immunization plays a vital role in preventing infectious diseases, significantly reducing morbidity and mortality worldwide. Indonesia's national immunization program has been in place since 1956, focusing on vulnerable groups such as infants and pregnant women. However, despite these efforts, immunization rates in Paku Alam Village, South Kalimantan, remain suboptimal, with 90% of the target population yet to complete basic immunization in 2023. Factors contributing to this gap include misinformation, vaccine hesitancy, and low health literacy among the population. Case presentation: In Paku Alam Village, only 27 out of the 30 targeted children for the 2023 immunization program received partial immunizations, with none completing the full schedule by mid-year. Misinformation spread via social media, coupled with fears about vaccine side effects, has fueled parental reluctance to immunize. Midwives and healthcare workers have struggled to combat these challenges due to a lack of effective communication tools and deep-rooted distrust in the healthcare system. Discussion: Addressing the immunization gap in Paku Alam Village requires a multifaceted approach, including educational interventions tailored to parents. These interventions should include visual aids, interactive discussions, and community-based outreach to improve vaccine knowledge and trust. Additional strategies like offering incentives, collaborating with early childhood education centers, and strengthening healthcare worker training are also critical. Building trust through culturally appropriate messaging from trusted community leaders is essential to overcoming vaccine hesitancy. Conclusion: The immunization program in Paku Alam Village faces challenges rooted in low parental knowledge and the spread of misinformation. However, targeted health education, collaboration between healthcare workers, schools, and community leaders, and incentivization strategies can improve immunization coverage. A comprehensive, multi-sectoral approach is required to meet the village's immunization goals.